2021
DOI: 10.4317/jced.58415
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of two artificial saliva-based polymers containing 0.1% pilocarpine for treatment of xerostomia: A randomized clinical pilot trial

Abstract: Background Topical agents are the mainstay in the treatment of xerostomia, a common complaint most frequently associated with salivary dysfunction. This study aimed to compared the efficacy and safety for xerostomia treatment of 2 artificial saliva preparations containing 0.1% pilocarpine, and, either sodium carboxymethylcellulose (SCMC), or, sodium polyacrylate (SPA). Material and Methods Thirty-one xerostomia patients were randomly allocated into either a SCMC-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…In earlier research, artificial saliva based on sodium carboxymethylcellulose (SCMC) was frequently used to treat the symptoms of xerostomia, owing to its moderate efficacy in relieving dry mouth symptoms. 18,19 Oh et al discovered that a saliva substitute made of carboxymethylcellulose may reduce the suffering of patients from dry mouth both during the day and at night, with significantly greater efficacy shown for patients with functional residual secretory capacity. 7 In this study, we mainly recruited people whose secretory glands were still functional.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier research, artificial saliva based on sodium carboxymethylcellulose (SCMC) was frequently used to treat the symptoms of xerostomia, owing to its moderate efficacy in relieving dry mouth symptoms. 18,19 Oh et al discovered that a saliva substitute made of carboxymethylcellulose may reduce the suffering of patients from dry mouth both during the day and at night, with significantly greater efficacy shown for patients with functional residual secretory capacity. 7 In this study, we mainly recruited people whose secretory glands were still functional.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the effects of pilocarpine mouthwash at concentrations ranging from 0.01 to 4% and have indicated that the effect increases with concentration [ 1 , 17 , 23 , 25 , 34 ]. Bernardi’s study examined the effects of 0.5, 1, and 2% pilocarpine mouthwashes in healthy volunteers and showed a dose-dependent increase in whole unstimulated saliva [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the sufferers have symptoms that impact their health and the social and emotional elements of their lives. It can also cause many short-term and long-term complications such as tooth caries, burning mouth sensation, periodontal diseases, dysgeusia, difficulty using dentures, and fungal infections resulting in reduced quality of life [ 1 5 ]. In addition, hyposalivation is when the unstimulated total salivary flow rate is less than 0.01 mL/min during awake hours [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their main purpose is to lubricate the mucous membrane and facilitate chewing, swallowing and speaking. Some preparations may be combined with pilocarpine which stimulates the salivary glands to produce more natural saliva [7,8]. Artificial saliva was in the past only rarely a subject of a clinical controlled trial as such.…”
Section: Topical Agents and Saliva Substitutesmentioning
confidence: 99%
“…Recently, several clinical trials with different formulations of artificial saliva with or without pilocarpine were published which suggests developments of new and improved preparations [8][9][10]. A study by Sarideechaigul et al [8] aimed to compare the efficacy and safety of xerostomia treatment of two artificial saliva formulations containing 0.1% pilocarpine, and, either sodium carboxymethylcellulose or, sodium polyacrylate. Thirty-one xerostomia patients with xerostomia were randomly allocated into either a carboxymethylcellulose-treated group (15 patients) or, a polyacrylate-treated group (16 patients).…”
Section: Topical Agents and Saliva Substitutesmentioning
confidence: 99%